CFD study of the transient wet gas flow behavior through orifice plate flow meters - Weise, Josiane; Baliño, Jorge L.; Paladino, Emilio E. (Elsevier, 2021)
Differential pressure flow meters are widely used in wet gas flow measurement, typically, combined with a method to determine the liquid fraction. An alternative with significant advantages for industry, in term of cost, operation and maintenance, is determining the liquid fraction based on its relation with the statistical parameters of transient differential pressure signal fluctuations. In this way, a single measurement device can provide mass flow rate and liquid fraction simultaneously. For this method to be more feasible in the wet gas flow measurement, it is essential to understand how the differential pressure signal fluctuations and the gas–liquid flow behavior at the restriction are correlated. On this basis, this paper presents a transient 3D Computational Fluid Dynamics (CFD) study of the wet gas flow through an orifice plate, operating under field conditions, using the two-fluid model. Steady-state results, calculated from the time averaging of the transient solution, for the over-reading OR parameter were validated with experimental field data and results obtained by correlations available in the literature, showing very good agreement. The transient results from simulations presented a trend in agreement with experimental data from the literature, showing a positive correlation of the standard deviation of differential pressure signal with liquid fraction upstream of the orifice plate. However, these results should be analyzed qualitatively due to model limitations, mainly related to the interfacial transfer closure in gas–liquid flows with changing phase morphologies. Despite this fact, some important insights regarding the 3D transient flow structure with a practical value were obtained from the model.
Keywords: Differential pressure fluctuations; Orifice plate meter; Over-reading; Two-fluid model; Wet gas